INOVASI STRATEGI PEMBELAJARAN KOLABORATIF DALAM MENINGKATKAN KETERAMPILAN DI SPM ULYA - fitriyah, Imro’atul (As-Sulthan Journal of Education, 2024)
The innovation of collaborative learning strategies at SPM Ulya aims to enhance students' skills in various aspects, including analytical skills, problem-solving, communication, and teamwork. This approach involves students in collaborative activities that encourage active participation and interaction among them. Collaborative learning is considered an effective method to address the educational challenges of the 21st century, where critical thinking, creativity, and cooperation skills are key to students' future success. By implementing this strategy, it is hoped that students can better understand the material in a more dynamic and applicable way, while also developing important social skills.